Eltrombopag in children with severe aplastic anemia. Issue 8 (15th April 2021) - Lesmana, Harry; Jacobs, Timothy; Boals, Michelle; Gray, Nathan; Lewis, Sara; Ding, Juan; Kang, Guolian; Hale, Melvanique; Weiss, Mitchell; Reiss, Ulrike; Wang, Winfred; Wlodarski, Marcin
Abstract: Background: Immunosuppressive therapy with horse antithymocyte globulin and cyclosporine currently remains the standard therapy for children with severe aplastic anemia (SAA) who lack human leukocyte antigen (HLA)‐identical sibling. The thrombopoietin receptor agonist eltrombopag has been recently approved for SAA patients 2 years and older. However, there are limited data on its safety and efficacy in pediatric cohorts. Methods: We conducted a retrospective study of patients ≤18 years old consecutively diagnosed with SAA between 2000 and 2018. Patients received either standard immunosuppressive therapy (IST‐Std) or IST with eltrombopag (IST‐Epag). The primary outcome was the objective response (OR), including partial and complete response (CR), at 6 and 12 months after starting therapy. Results: We identified 16 patients receiving IST‐Std and nine IST‐Epag treatment (seven of nine as upfront therapy and two of seven after previously failed IST). The OR at 6 and 12 months in IST‐Std arm was 71% and 100%, with CR in 29% and 58%, respectively. Seven patients receiving upfront IST‐Epag had OR at 6 and 12 months, with two of seven (29%) achieving CR at 6 and 12 months. Two patients who previously failed standard IST did not respond to eltrombopag. No significant differences were observed in both cohorts with regard to infections. One IST‐Epag‐treated patient developed transient grade 3 transaminitis. Finally, no changes in paroxysmal nocturnal hemoglobinuria (PNH) clone size and cytogenetic abnormalities were seen in either cohort. Conclusion: The addition of eltrombopag to standard IST was well tolerated and resulted in satisfactory hematological response at 6 and 12 months in this single‐institution experience. A larger cohort with longer follow‐up is required to assess response durability.